PsycEXTRA Dataset 1998
DOI: 10.1037/e509252006-001
|View full text |Cite
|
Sign up to set email alerts
|

Matching Traffic Safety Strategies to Youth Characteristics: A Literature Review of Cognitive Development

Abstract: In an effort to reduce the high crash rate and resulting injuries of young drivers, the National Highway Traffic Safety Administration has sponsored research to assess the factors responsible for this heightened crash risk and to determine the implications for traffic safety programs. As part of this research, this review of research literature was conducted to determine what is known about cognitive development and information processing capabilities of youth. The goal of the project was to ascertain how traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 437 publications
0
9
0
1
Order By: Relevance
“…( 2 ) Accordingly, it is appropriate to identify the individual patterns of higher risk leading to speeding and accidents. For instance, young drivers tend to be cognitively less mature in their general decisional abilities ( 9 ) and car crashes are positively correlated with decisional driving errors, ( 10 ) which may be manifestations of such immaturity. For example, Summala ( 5 ) and Wilde ( 7,8 ,) have argued that both accident‐prone young drivers and youth in the workplace tend to distort the actual safety risks that they incur.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…( 2 ) Accordingly, it is appropriate to identify the individual patterns of higher risk leading to speeding and accidents. For instance, young drivers tend to be cognitively less mature in their general decisional abilities ( 9 ) and car crashes are positively correlated with decisional driving errors, ( 10 ) which may be manifestations of such immaturity. For example, Summala ( 5 ) and Wilde ( 7,8 ,) have argued that both accident‐prone young drivers and youth in the workplace tend to distort the actual safety risks that they incur.…”
Section: Introductionmentioning
confidence: 99%
“…Rather, researchers should aim for the early identification of young drivers at relatively greater risk for having speeding tickets and accidents. Such an identification of individual driving‐related attitudes and personality ( 9 , 11, 12 ) could then be incorporated into driver education programs to augment the training of those at risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This is because many other variables affect young drivers behind the wheel that result in increased crash rates. 20 Despite driver education, a study conducted for the Commonwealth of Virginia, for example, showed that for use of alcohol and other drugs, speeding, reckless driving, improper driving, high risk behavior, seat belt violations, and administrative violations, the percentage of convicted drivers in their late teens was several times higher than for any other age group. 21 No study conducted in more than 30 years has shown that teenage driver education effectively reduces either the rate or the severity of young driver crash involvement.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…En ese sentido, se le conceptualiza como un problema cada vez más complejo para los conductores, quienes se enfrentan constantemente situaciones de elección y estimación de riesgo (Eby y Molnar, 1998). Al respecto, Matthews y Moran (1986) y Alonso, Esteban, Calatayud, Montoro y Alamar (2004), han referido que los conductores se caracterizan por carecer de una amplia experiencia empírica en la conducción y estar influenciados por factores socioculturales, es decir, experiencias y sucesos que tienen lugar en su entorno inmediato, los cuales son empleados para estimar su conducta de riesgo vial.…”
Section: Introductionunclassified